Plastic Shrinkage Cracking in Concrete - Sayahi, Faez (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2016)
Early-age (up to 24 hours after casting) cracking may become problematic in any concrete structure. It can damage the aesthetics of the concrete member and decrease the durability and serviceability by facilitating the ingress of harmful material. Moreover, these cracks may expand gradually during the member’s service-life due to long-term shrinkage and/or loading. Early-age cracking is caused by two driving forces: 1) plastic shrinkage cracking which is a physical phenomenon and occurs due to rapid and excessive loss of moisture, mainly in form of evaporation, 2) chemical reactions between cement and water which causes autogenous shrinkage. In this PhD project only the former is investigated. Rapid evaporation from the surface of fresh concrete causes negative pressure in the pore system. This pressure, known as capillary pressure, pulls the solid particles together and decreases the inter-particle distances, causing the whole concrete element to shrink. If this shrinkage is hindered in any way, cracking may commence. The phenomenon occurs shortly after casting the concrete, while it is still in the plastic stage (up to around 8 hours after placement), and is mainly observed in concrete elements with high surface to volume ratio such as slabs and pavements. Many parameters may affect the probability of plastic shrinkage cracking. Among others, effect of water/cement ratio, fines, admixtures, geometry of the element, ambient conditions (i.e. temperature, relative humidity, wind velocity and solar radiation), etc. has been investigated in previous studies. In this PhD project at Luleå University of Technology (LTU), in addition to studying the influence of various parameters, effort is made to reach a better and more comprehensive understanding about the cracking governing mechanism. Evaporation, capillary pressure development and hydration rate are particularly investigated in order to define their relationship. This project started with intensive literature study which is summarized in Papers I and II. Then, ...